CHITOSAN NANOPARTICLE-ENCAPSULATED ACANTHOSPERMUM HISPIDUM FOR ENHANCED IN VITRO ANTIOXIDANT, ANTIMICROBIAL, AND IN VIVO ANTICANCER ACTIVITIES AGAINST HEPATOCELLULAR CARCINOMA - Ahmad, Shehu Muazu; Ahmad, Bashir; Lawal, Misbahu Koramar Boko (FUDMA Journal of Sciences, 2025)
Hepatocellular carcinoma (HCC) remains a major global health challenge, driven by oxidative stress, chronic inflammation, and limited treatment options. Medicinal plants rich in bioactive phytochemicals offer promising therapeutic alternatives, but many suffer from poor solubility, instability, and low bioavailability, limiting their clinical usefulness. Acanthospermum hispidum, traditionally used for treating infections and inflammatory disorders, contains potent antioxidant, antimicrobial, anti-inflammatory, and anticancer compounds. However, its therapeutic potential requires enhancement through an efficient delivery system.This study investigates the therapeutic effectiveness of A. hispidum extract encapsulated in chitosan nanoparticles (AH-CNP) to improve its stability and bioavailability. The extract (10 mg/mL) was incorporated into a 0.5% chitosan solution, yielding nanoparticles with an encapsulation efficiency of 90 ± 0.33%. Antioxidant evaluation using DPPH assay showed that AH-CNP had a lower IC₅₀ value (4.10 µg/mL) compared to free extract (4.40 µg/mL) and plain chitosan nanoparticles (5.50 µg/mL), indicating improved radical-scavenging activity. AH-CNP also exhibited enhanced antimicrobial activity, producing the widest zone of inhibition (20.50 ± 1.20 mm against E. coli at 8000 µg/mL).In vivo assessment in an HCC-induced rat model demonstrated that AH-CNP (300 mg/kg) significantly reduced liver enzyme levels (ALT, AST, ALP), improved liver function, and restored hepatic architecture. Additionally, pro-inflammatory markers (TNF-α, IL-6, CRP, IL-1β) were markedly suppressed, confirming its anti-inflammatory potential.Overall, the findings suggest that chitosan nanoparticle-encapsulated A. hispidum is a promising nanomedicine for managing HCC and oxidative stress-related diseases. Further studies are needed to evaluate its long-term safety and clinical applicability.